Role of Microbiota and Tryptophan Metabolites in the Remote Effect of Intestinal Inflammation on Brain and Depression - Waclawiková, Barbora (Pharmaceuticals (Basel), 2018)
The human gastrointestinal tract is inhabited by trillions of commensal bacteria collectively known as the gut microbiota. Our recognition of the significance of the complex interaction between the microbiota, and its host has grown dramatically over the past years. A balanced microbial community is a key regulator of the immune response, and metabolism of dietary components, which in turn, modulates several brain processes impacting mood and behavior. Consequently, it is likely that disruptions within the composition of the microbiota would remotely affect the mental state of the host. Here, we discuss how intestinal bacteria and their metabolites can orchestrate gut-associated neuroimmune mechanisms that influence mood and behavior leading to depression. In particular, we focus on microbiota-triggered gut inflammation and its implications in shifting the tryptophan metabolism towards kynurenine biosynthesis while disrupting the serotonergic signaling. We further investigate the gaps to be bridged in this exciting field of research in order to clarify our understanding of the multifaceted crosstalk in the microbiota–gut–brain interphase, bringing about novel, microbiota-targeted therapeutics for mental illnesses.